2017
DOI: 10.1080/09515089.2017.1367767
|View full text |Cite
|
Sign up to set email alerts
|

Lottery judgments: A philosophical and experimental study

Abstract: In this paper, we present the results of two surveys that investigate subjects' judgments about what can be known or justifiably believed about lottery outcomes on the basis of statistical evidence, testimonial evidence, and "mixed" evidence, while considering possible anchoring and priming effects. We discuss these results in light of seven distinct hypotheses that capture various claims made by philosophers about lay people's lottery judgments. We conclude by summarizing the main findings, pointing to future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…This is my proposed solution to the legal puzzle of statistical evidence. [Smith 2018[Smith : 1209[Smith -1210 Littlejohn's argument Littlejohn holds that the reasonableness of a belief should be judged against the standard of acquiring knowledge, something that purely statistical evidence cannot yield. With this in mind, he endorses the following principle:…”
Section: Smith's Argumentmentioning
confidence: 99%
See 2 more Smart Citations
“…This is my proposed solution to the legal puzzle of statistical evidence. [Smith 2018[Smith : 1209[Smith -1210 Littlejohn's argument Littlejohn holds that the reasonableness of a belief should be judged against the standard of acquiring knowledge, something that purely statistical evidence cannot yield. With this in mind, he endorses the following principle:…”
Section: Smith's Argumentmentioning
confidence: 99%
“…Firstly, cases-particularly sexual offences-where the only incriminating evidence is DNA material are not 35 For instance, surveys of judges on their view of the BRD standard (discussed in Solan 1999) support this assumption. 36 Ebert et al (2018) found regarding lottery cases that subjects are more likely to ascribe justified belief (but not knowledge) when the lottery is much larger-i.e. when the chance of error is much lower.…”
Section: Rehabilitating Statistical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“… The reluctance to ascribe liability on the basis of statistics is known as the Wells Effect after an empirical study of mock‐jurors (Wells, 1992). This is a piece with a broader phenomenon, often illustrated with lotteries , whereby subjects are reluctant to treat statistical evidence on par with other types of evidence (see Ebert, Smith, & Durbach, 2018). …”
mentioning
confidence: 99%
“…SeeBackes (2019) for a discussion of the other direction: using legal cases as evidence for theories in epistemology.18 In addition to the papers cited in-text, seeBuchak (2014) for an early influential endorsement of this analogy.19 For empirical study of attitudes towards lottery propositions under different conditions, seeEbert et al (2018).…”
mentioning
confidence: 99%